Diagnostic approach to low back pain - Hatice Resorlu (SERNEV, 2023)
Low back pain is an important cause of pain referrals in the primary care setting. Overall, 85% of initial admissions are considered to be nonspecific low back pain that resolves in a few weeks without the need for additional evaluation. Myofascial pain, lumbar disc herniation, spinal stenosis, facet joint and disc degeneration, and sacroiliac joint pathologies are common causes of mechanical low back pain. Non-mechanical low back pain includes infections of the vertebral corpus and disc, malignant tumors and metastases, and inflammatory diseases. Red flag symptoms suggestive of serious diseases should be evaluated in all patients with low back pain, and the diagnosis process should be accelerated in patients with these symptoms. The so-called "yellow flags" associated with chronic low back pain include psychosocial factors. In the diagnosis process, pain relief is observed in patients with non-specific low back pain without the need for imaging methods. Laboratory tests and imaging methods can be used to distinguish other causes of low back pain.